Murder as an Instance of Local Rhetoric in the Performance of Israeli Drama: A Phenomenological Strategy - Kaynar, Gad (Hebrew studies, 2002)
The article reads the performance of Murder from a phenomenological perspective, which caters for the interactive relationships between the theatrical text and the image of the spectator implied in and by it, based on the local experiential and libidinal, rather than cerebral, reality-convention of this indigenous addressee. This kind of rhetoric, which informs the theatrical text of most Israeli plays inasmuch as it affects the generation of the implied spectator's collective identity, is paradigmatically concretized in Murder through one of the central integrative images in the performance: the image of the sand that covers the stage and drops from above—the sand in which the train of atrocities is performed—conceived of not as a mere iconic image, but as the thing itself in its material-conceptual reality. The article goes on to show how the metamorphosed sensory effect of the sand is supported on the visual level by the optic rhetoric of Murder's stage design.